Interpreters Between Concepts Quranic And problematic External certifications (Journal of Imam Al-Kadhim College, 2024)
Abstract Some of the blessed Qur’an texts represent the truth and clarification of the application of Qur’an concepts to the conditions for which they were cited exclusively, and sometimes others are not accepted, and at other times they give multiple meanings to a single Qur’an concept according to the multiple connotations that surround the Qur’an  text, in addition to the fact that the authenticity is not limited to specific individuals, times, and places, which has led to until the emergence of differences between commentators in understanding the Qur’an  text based on whether the concept applies to the source or not, the revelation of the verse in a group or individual does not require its specification to that context as long as the wording is (general), but if the wording is (specific) through its appearance in the Qur’an, or its specificity according to the authentic narrations contained in the explanation of the reasons for the revelation, it is necessary to have a single source that applies to specific individuals and does not apply to othersThe concept has always been distinguished by its stability, as commentators consider it to be a temporary one that does not accept change or replace., as for (the authentication), it is variable according to a number of clues, including the Meccan  and  Madina  verse and, the reasons for the revelation and the matter of the revelation, and the abrogated and omitted , the research has pointed to the theory of the unity of the concept and the multiplicity of the authenticity. Which some thinkers have adopted in directing meaning and deriving judgments, by presenting applied models that show both cases - the application of the concept to a single external validity, and the multiple external certifications of a single concept , therefore, the research seeks to reveal the opinions of commentators on the truth of the concept and the authenticity and to explain the extent to which it applies or not to the external credibility in an attempt to clarify the paths of the Qur’an facts included under the general concepts in the Qur’an text.